Wunderkammer: the performance showcase as critical performative pedagogy. Issue 3 (3rd July 2019) - Huber, Aubrey A.; McRae, Chris
ABSTRACT: The performance showcase is a rich opportunity to employ critical performative pedagogy as an embodied engagement with, interrogation of, and disruption to institutional and ideological structures and practices. Wunderkammer (cabinet of curiosities): A Performance Showcase radically actualizes critical performative pedagogy by attending to, collecting, and curating the embodied labor of the performance classroom and curriculum. We include a descriptive account of Wunderkammer that invites you, the reader, to imagine and experience a version of the showcase, and that emphasizes our process and choices as curators.